Physical manipulation of biological and chemical syntheses for nanoparticle shape and size control - Ogale, Satishchandra B.; Ahmad, Absar; Pasricha, R.; Dhas, Vivek V.; Syed, A. (Applied Physics Letters, 2006)
A nanosynthesis scheme is demonstrated which renders excellent control of nanoparticle shape, size, and dispersity in a solution based synthesis process. The scheme, termed as percolative microcavity synthesis, involves the use of a granular medium with percolative microcavities which facilitate nearly similar grain size/shape dependent reaction zones limiting intrinsic growth inhomogeneities, enabling particle size/shape control. The viability of the process is demonstrated for the synthesis of gold nanoparticles by a plant extract based biological method as well as a chemical method. (c) 2006 American Institute of Physics.